2004
DOI: 10.1051/forest:2004084
|View full text |Cite
|
Sign up to set email alerts
|

Modelling juvenile-mature wood transition in Scots pine (Pinus sylvestris L.) using nonlinear mixed-effects models

Abstract: -Nonlinear mixed-effects-models are applied successfully to estimate the cambial age of juvenile-mature wood transition in Scots pine sample trees from slow-grown stands. Till now segmented regression models are applied separately for each pith-to-bark-profile of wood density. The nonlinear mixed-effects-model overcomes this limitation while consistently and efficiently estimating the transition point for the whole sample. Furthermore standard errors can be calculated and impacts of stand and tree variables on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
2

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(47 citation statements)
references
References 25 publications
2
43
0
2
Order By: Relevance
“…In the case of volumetric shrinkage, the variation explained by the fixed effects was 36.4%, with an additional 19.6% explained by the random effects. These results indicate the importance of considering the random effects in modelling physical properties variation along the stem, as considered for Scots pine and other species (Mutz et al, 2004). It should be considered that, although no direct effect of height in the stem was considered in these models, the negative effect of ring width and the increase in basic density outward from the pith of the stem result in a necessary decrease in density from the base to the tree top, as considered in other models (Kellomäki et al, 1999).…”
Section: Models Proposed To Estimate Basic Density and Volumetric Shrmentioning
confidence: 97%
See 1 more Smart Citation
“…In the case of volumetric shrinkage, the variation explained by the fixed effects was 36.4%, with an additional 19.6% explained by the random effects. These results indicate the importance of considering the random effects in modelling physical properties variation along the stem, as considered for Scots pine and other species (Mutz et al, 2004). It should be considered that, although no direct effect of height in the stem was considered in these models, the negative effect of ring width and the increase in basic density outward from the pith of the stem result in a necessary decrease in density from the base to the tree top, as considered in other models (Kellomäki et al, 1999).…”
Section: Models Proposed To Estimate Basic Density and Volumetric Shrmentioning
confidence: 97%
“…Scots pine is considered to show a clear transition between juvenile and mature wood, which has been estimated at a cambial age of 22 years (Mutz et al, 2004;Zobel and van Buijtenen, 1989).…”
Section: Introductionmentioning
confidence: 99%
“…The application of this model determined that the age of the pieces of old wood was from 25 to 30 years. Other studies on the same wood presume it to be mature at this age [25]. However, as the cambial age is quite variable between trees of the same forest and between different regions of provenance, particularly in conifers, the old wood samples were considered to be of juvenile wood in accordance with the specific preliminary study on the forest from which they came, in terms of the number of rays and the length of the tracheids, which enabled it to be established that up to ring 40, with a 5% confidence level, the juvenilemature cambial age did not occur [22].…”
Section: Methodsmentioning
confidence: 99%
“…In the opinion of the authors, density of late wood leads to an overestimation of transition age in relation to ring density and the share of late wood in annual increments in diameter. Based on studies of density of late wood zones conducted on discs collected from 99 stems of Scots pine (Pinus sylvestris L.) coming from the height of 4 m, Mutz et al (2004) identified the boundary between juvenile and mature wood between the 18 th and 27 th annual rings. After several statistical analyses were conducted and a square linear model was specified, the transition boundary was established at cambial age of 21 years.…”
Section: Resultsmentioning
confidence: 99%